New WC-Cu composites for the divertor in fusion reactors - Dias, Marta (2020)
ABSTRACT: The requirements for the divertor components of future fusion reactors are challenging and therefore a stimulus for the development of new materials. In this paper, WC-Cu composites are studied for use as thermal barrier between the plasma facing tungsten tiles and the copper-based heat sink of the divertor. Composite materials with 50% vol. WC were prepared by hot pressing and characterized in terms of microstructure, density, expansion coefficient, elastic modulus, Young's modulus and thermal diffusivity. The produced materials consisted of WC particles homogeneously dispersed in a Cu matrix with densifications between 88% and 98%. The sample with WC particles coated with Cu evidenced the highest densification. The thermal diffusivity was significantly lower than that of pure copper or tungsten. The sample with higher densification exhibits a low value of Young's modulus (however, it is higher compared to pure copper), and an average linear thermal expansion coefficient of 13.6 x 10(-6) degrees C-1 in a temperature range between 100 degrees C and 550 degrees C. To estimate the behaviour of this composite in actual conditions, a monoblock of the divertor in extreme conditions was modelled. The results predict that while the use of WC-Cu interlayer leads to an increase of 190 degrees C on the temperature of the upper part of the monoblock when compared to a pure Cu interlayer, the composite will improve and reduce significantly the cold-state stress between this interlayer and the tungsten.